Effect of fluid-structure-thermal Interaction on Mechanical Yaw Thrust Vectoring Efficiency of a 2d Nozzle - Vashistha, Rohit; Gopal, K. V. N.; Gogoi, A. (Journal of Structural Engineering, 2025)
In a tailless flying wing type aircraft, achieving yaw control is an engineering challenge. The limitation posed due to absence of vertical tail is overcome by deflecting engine exhaust jet in the yaw plane to achieve the required yaw moment. Various computational fluid dynamics and fluid structure interaction analysis were carried out to establish the effectiveness of the thrust vectoring for rocket nozzle but no such analysis is carried out so far for 2D rectangular convergent nozzle characteristic for tailless flying wing aircraft which needs 2D thrust vectoring for yaw control. Accurate estimation of the yaw moment is essential for accurate control law functioning. In the present work, the effect of fluid-structure-thermal interaction on thrust vectoring effectiveness for yaw control is analyzed for case of 5 degree and 10 degree vane deflection. The thermal heating resulted in an increase in the nozzle throat area. In case of under expanded nozzle, increase in throat area allows greater chocked mass flow rate which results in an increase in thrust. The vane deformation due to pressure loading give rise to reduction in the desirable velocity component (y-component of velocity) which leads to reduction in effectiveness of thrust vectoring.